Problems and Prospects of Part-Time Employment among Studentswith special reference to Palakkad District in Kerala. (International Journal of Food and Nutritional Sciences, 2022)
In contemporary times, many students are engaging in part-time employment to support their studies and assist their families due to the escalating costs of education. These part-time jobs have their own advantages and disadvantages. This research investigates into the challenges and opportunities associated with part-time employment for students in the Palakkad district of Kerala. A random sample of 120 students engaged in part-time work was chosen for this study, and data was gathered using a structured questionnaire. The research also explores the motivations driving students to take up part-time jobs. Various analytical methods such as percentage analysis, mean, standard deviation, one-way ANOVA, and others were employed for data analysis. The findings of the study indicate that the prospects of part-time jobs are promising, with a mean score of 4.12. The research highlights that the primary benefits of students taking on part-time employment include the development of time management skills, acquisition of money management skills, bolstering of self-confidence, enhancement of interpersonal skills, gaining valuable experience for future employment, and achieving financial independence. Notably, these aspects all received a mean rating of over 4, and a majority of the respondents expressed satisfaction with them. On the flip side, the primary challenges associated with part-time jobs include time constraints for studying, lack of job experience, limited computer literacy, educational qualifications, deficient English communication skills, difficulty adjusting to the work environment, absence of interpersonal relationships, and the search for suitable employment. The study also observed significant disparities in the prospects and challenges of part-time employment based on the respondents' qualifications.